2019
DOI: 10.3390/technologies7030049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, Optimization, and Characterization of Magnetic Photonic Crystal Structures and Thin-Film Material Layers

Abstract: The development of magnetic photonic crystals (MPC) has been a rapidly evolving research area since the late 1990s. Magneto-optic (MO) materials and the techniques for their characterization have also continually undergone functional and property-related improvements. MPC optimization is a feature-rich Windows software application designed to enable researchers to analyze the optical and magneto-optical spectral properties of multilayers containing gyrotropic constituents. We report on a set of computational a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This combinatorial approach employs a custom-built spectrum-fitting software in conjunction with the Swanepoel envelope method (SWEM). The following operational steps are conducted for the evaluation of optical constants: (i) Calculation of the refractive index data and film thickness using the SWEM method [78]; (ii) use of the calculated index data (from SWEM), in conjunction with least-square fitting to derive the real part of the index from Cauchy’s formula (n (λ) = a + b/λ 2 ); (iii) use of the refractive index data (derived from Cauchy’s formula) in magnetic photonic crystal (MPC) analysis software [79] to model and fit the measured transmission spectra; and (iv) from this fitting process, reconfirm the film thicknesses and derive the absorption coefficient spectra of the films. The wavelength-dependent index (n) data (calculated based on Cauchy’s dispersion formula) for the amorphous garnet and garnet-oxide precursor thin layers deposited on glass (Corning Eagle XG, 0.5 mm thick) substrates yield the following spectral dependency for BiDyIG sample, n = 2.1906 + 0.0459/λ 2 , and for BiDyIG:Bi 2 O 3 (17 vol.…”
Section: Garnets Garnet-oxide Composites and Multilayer Structurmentioning
confidence: 99%
“…This combinatorial approach employs a custom-built spectrum-fitting software in conjunction with the Swanepoel envelope method (SWEM). The following operational steps are conducted for the evaluation of optical constants: (i) Calculation of the refractive index data and film thickness using the SWEM method [78]; (ii) use of the calculated index data (from SWEM), in conjunction with least-square fitting to derive the real part of the index from Cauchy’s formula (n (λ) = a + b/λ 2 ); (iii) use of the refractive index data (derived from Cauchy’s formula) in magnetic photonic crystal (MPC) analysis software [79] to model and fit the measured transmission spectra; and (iv) from this fitting process, reconfirm the film thicknesses and derive the absorption coefficient spectra of the films. The wavelength-dependent index (n) data (calculated based on Cauchy’s dispersion formula) for the amorphous garnet and garnet-oxide precursor thin layers deposited on glass (Corning Eagle XG, 0.5 mm thick) substrates yield the following spectral dependency for BiDyIG sample, n = 2.1906 + 0.0459/λ 2 , and for BiDyIG:Bi 2 O 3 (17 vol.…”
Section: Garnets Garnet-oxide Composites and Multilayer Structurmentioning
confidence: 99%
“…To investigate the effects of post-deposition oxygen plasma treatment on the optical and magneto-optical behaviours of Bi 2.1 Dy 0.9 Fe 3.9 Ga 1.1 O 12 type thin films, we derived the optical absorption coefficients, measured the specific Faraday rotation and calculated the MO figure of merit at a certain spectral wavelength (532 nm). The transmission spectra of all annealed garnet layers were spectrally fitted with the modeled transmission spectra to determine the optical absorption on the garnet layers by using the MPC software reported in Reference [ 42 ]. The plasma-treated samples showed slightly higher specific Faraday rotation at 532 nm compared to the non-treated garnet samples and this was repeatedly observed in all batches of plasma-treated annealed samples.…”
Section: Resultsmentioning
confidence: 99%
“…The paper written by Vasiliev et al [12] reported a set of computational algorithms to optimize the design and the optical or magneto-optical spectral analysis of 1D magnetic photonic crystals together with a windows software implementation. They also reported the methods and algorithms to obtain absorption coefficient spectral dispersion datasets for new materials.…”
mentioning
confidence: 99%